Political Correctness and the Destruction of Social Order Chronicling the Rise of the Pristine Self - Schwartz, Howard S; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint: Palgrave Macmillan), 2016)
This book develops a psychoanalytic theory of political correctness and the pristine self, which is defined as a self touched by nothing but love. It explores the damage that political correctness can do to social order. Applications include the breakdown of social capital, the financial crisis, and Occupy Wall Street. Long an issue for conservatives, alarm over political correctness has now spread to the liberal side of the political spectrum. As Schwartz argues, all have reason to be concerned. The psychology that underlies political correctness has the potential to be extremely destructive to social organization on every level. Schwartz discusses the primitive roots of political correctness and, through the use of case studies, shows its capacity for ruination. The book focuses on a transformation in the idea of the self, and specifically the rise of the pristine self. The problem is that, in truth, the world does not love us. This puts the pristine self at war with objective reality.
Introduction: The Nature of Political Correctness -- The Pristine Self and the Psychodynamics of the Anti-Bullying Movement -- Putnam's Paradox: Diversity, Destruction of Community, and Anti-oedipal Psychology -- Anti-oedipal dynamics in the sub-prime loan debacle: The case of a study by the Boston Federal Reserve Bank -- The British Riots of 2011 -- Reality and Truth in the Politically Correct Organization: The Case of the Dan Rather Memo Debacle at CBS News -- What was the Occupy Wall Street Protest a Protest of? -- Conclusion: Finessing The Existential Question.
Keywords: Applied psychology; Psychoanalysis; Community and Environmental Psychology